A wildlife tolerance model and case study for understanding human wildlife conflicts. (September 2016) - Kansky, Ruth; Kidd, Martin; Knight, Andrew T.
Abstract: Human-wildlife conflict (HWC) is a complex conservation issue and acknowledging the human dimensions of the problem is critical. Here we propose the Wildlife Tolerance Model (WTM), a novel theoretical framework to identify key drivers of tolerance to living with damage-causing wildlife. The WTM proposes an outer model, where the extent to which a person experiences a species determines perceptions of cost s relative to benefits of living with a species. This in turn determines tolerance. A second component, the inner model predicts eleven variables that may further drive perceptions of costs and benefits . In the current paper we test the outer model while in a forthcoming publication we test the inner model using a case study of human-baboon conflict in Cape Town, South Africa. Using Partial Least Squares Structural Equation Modeling we found support for the outer model . Experience explained 30% of variance in costs and benefits and 60% of tolerance was explained by perceptions of costs and benefits . Intangible costs and intangible benefits equally contributed to driving tolerance but tangible costs had no significant effect on tolerance . Separating two dimensions of experience, (i) exposure to a species explained costs more than benefits, and (ii) positive experiences explained intangible cost s and benefits more than tangible costs while negative experiences equally explained costs and benefits . We discuss management implications of the findings and conclude that the WTM could be a useful diagnostic tool and theoretical framework to inform management interventions and policies to mitigate HWC. Highlights: We present a Wildlife Tolerance Model to identify key factors driving tolerance towards animals We tested the model using a case study of urban baboons and found support for the model 60% of tolerance towards baboons was explained by perceptions of costs and benefits. 30% of experience of baboons was explained by perceptions of costs and benefits Intangible costs and benefits equally contributed to explaining tolerance but tangible costs had no significant effect.